Millimeter-wave study of London penetration depth temperature dependence in Ba(Fe0.926Co0.074)2As2 single crystal - Barannik, A.A.; Glamazdin, V.V.; Prozorov, R.; Canfield, P.C.; Skresanov, V.N.; Vitusevich, S.A.; Tanatar, M.A.; Ni, N.; Cherpak, N.T.; Torokhtii, and K.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
In-plane surface Ka-band microwave impedance of optimally doped single crystals of the Fe-based superconductor Ba(Fe0.926Co0.074)2As2 (Tc = 22.8 K) was measured. Sensitive sapphire disk quasi-optical resonator with high-Tc cuprate conducting endplates was developed specially for Fe-pnictide superconductors. It allowed findingtemperature variation of London penetration depth in a form of power law, namely Δλ(T) ~ Tn with n = 2.8 from low temperatures up to at least 0.6Tc consisted with radio-frequency measurements. This exponent points towards nodelessstate with pairbreaking scattering, which can support one of the extended s-pairing symmetries. The dependence λ(T) at low temperatures is well described by one superconducting small-gap (Δ @ 0.75 in kTc units, where k is Boltzman coefficient) exponential dependence.